Cerebral Toxoplasmosis with Preserved CD4 Count (>300 cells/µL) in the HAART Era: Unmasking Immune Reconstitution Inflammatory Syndrome and the Diagnostic Utility of Cotrimoxazole - I Made Eryana; Made Nopriantha (Archives of The Medicine and Case Reports, 2025)
Cerebral toxoplasmosis (TE) typically presents in HIV-positive patients with severe immunosuppression (CD4 <100 cells/µL). However, in the era of Highly Active Antiretroviral Therapy (HAART), presentations have become atypical. We report a rare case of TE in a patient with a preserved CD4 count (>300 cells/µL), highlighting the phenomenon of unmasking immune reconstitution inflammatory syndrome (IRIS). A 22-year-old female, HIV-positive on a Tenofovir-Lamivudine-Efavirenz (TLE) regimen for one month, presented with subacute hemicrania, focal motor seizures, and complex visual hallucinations (zoopsia). Despite a CD4 count of 307 cells/µL and a suppressed viral load (<40 copies/mL), Contrast-Enhanced Computerized Tomography (CE-CT) revealed multiple ring-enhancing lesions with significant perilesional edema. The patient was diagnosed with TE-associated Unmasking IRIS. Due to the unavailability of Pyrimethamine, she was treated with high-dose Cotrimoxazole (960 mg q6h). Significant clinical improvement was observed by day 4, characterized by the cessation of seizures and hallucinations. Follow-up at two weeks confirmed sustained neurological recovery. In conclusion, a preserved CD4 count does not exclude opportunistic infections in the early post-HAART period. This case underscores the diagnostic pitfall of immune discordance and validates the efficacy of Cotrimoxazole as a primary therapeutic intervention in resource-limited settings.